ENDOMETRIOSIS OF THE CECUM AND APPENDIX: REVIEW OF LITERATURE. - Bandeira Domiciano, Carolina; de Araújo Alves , Priscilla Anny; Xavier da Nóbrega Pereira, Ana Livia Gadelha; Gadelha e Xavier, Beatriz; Nascimento de Oliveira, Deborah Cristina; de Carvalho Nobre Felipe, Daniel Hortiz; Camilo Neto, Geraldo; Costa Filho, Aníbal (Brazilian Journal of Implantology and Health Sciences, 2023)
Endometriosis is a benign, chronic, inﬂammatory and estrogen dependent pathology in which there is the implantation of functional extrauterine endometrial tissue. Pelvic and abdominal endometriosis are the most frequent presentations and, in these forms, ectopic endometrial implantation aﬀects the lesser pelvis, uterosacral ligaments, ovaries, uterine tubes, urinary and gastrointestinal tracts. Some symptoms such as altered bowel habits, pelvic pain, infertility and bleeding during bowel movements are present. In this work the focus is on the manifestations of endometriosis in the appendix and cecum. The use of imaging tests, such as transrectal and transvaginal ultrasonography, magnetic resonance imaging and colonoscopy are important tools used, however, the gold standard is videolaparoscopy with biopsy to conﬁrm the anatomopathological ﬁndings. The surgical strategy is related to the degree of impairment and must take into account the eradication of the disease together with the preservation of fertility. Therefore, the importance of evaluating and treating all areas that endometriosis aﬀects is clear, with a multidisciplinary approach by general surgeons and gynecologists, in order to investigate, diagnose and correctly address the disease in an organized and correct way.